Twenty Sixth IEEE/CPMT International Electronics Manufacturing Technology Symposium (Cat. No.00CH37146)
DOI: 10.1109/iemt.2000.910730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voids on the reliability of BGA/CSP solder joints

Abstract: Voids in solderjoints have been considered as a defect in electronics assembly. The factors that affect void formation are complex and involve the interaction of many other factors. There are no established standards for void size and void area in a solder joint for it to be deemed defective. Inspection criteria have been very subjective. The effect of voids on the reliability of a BGNCSP solder joint may depend not only on the size, but also on other factors such as frequency and location. This study focussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…A slow ramp-up of 1.5 K/s was used to significantly improve the DT of the board-level by decreasing its average from 11.22 to 7.74 K. The bridging defects were eliminated, as shown in the optimal condition in Figure 12. Moreover, both conditions also showed that the voids remained less than 50 per cent of the Figure 10 Comparison of the initial and optimal reflow profiles of the coldest solder joint (Yunus et al, 2003). A fast cooling rate of 3 K/s during the initial condition not only causes internal cracking of the solder joints, but also causes interface delamination (Hu et al, 2010) between the FR-4 PCBs, as shown in Figure 13(a).…”
Section: Experimental Comparison With Initial Process Parameter Settingsmentioning
confidence: 90%
“…A slow ramp-up of 1.5 K/s was used to significantly improve the DT of the board-level by decreasing its average from 11.22 to 7.74 K. The bridging defects were eliminated, as shown in the optimal condition in Figure 12. Moreover, both conditions also showed that the voids remained less than 50 per cent of the Figure 10 Comparison of the initial and optimal reflow profiles of the coldest solder joint (Yunus et al, 2003). A fast cooling rate of 3 K/s during the initial condition not only causes internal cracking of the solder joints, but also causes interface delamination (Hu et al, 2010) between the FR-4 PCBs, as shown in Figure 13(a).…”
Section: Experimental Comparison With Initial Process Parameter Settingsmentioning
confidence: 90%
“…(2) We must let the gasses discharged from the molten solder. 5. Degassing mechanism Bubble Behavior in Molten Solder is shown as follows:…”
Section: Fig 6 Courses Contribute To Voids Formationmentioning
confidence: 99%
“…Big voids, especially greater than 50% of the solder joint area, decrease the mechanical robustness of the solder joints. However, there was no statistical significance of the effect of small voids on the mechanical robustness of solder joint [5]. In this study, maximum void size in one solder joint was used to identify the void class according to the international void classification standard (IPC-7095B) shown in table 3 [6].…”
Section: B Void Characterizationmentioning
confidence: 99%